2017
DOI: 10.1002/cphc.201701058
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐site Cooperativity in Alkali‐Metal‐Exchanged Faujasites for the Production of Biomass‐Derived Aromatics

Abstract: The catalytic Diels–Alder cycloaddition–dehydration (DACD) reaction of furanics with ethylene is a promising route to bio‐derived aromatics. The reaction can be catalyzed by alkali‐metal‐exchanged faujasites. Herein, the results of periodic DFT calculations based on accurate structural models of alkali‐metal‐exchanged zeolites are presented, revealing the fundamental roles that confinement and the nature of the exchangeable cations in zeolite micropores have in the performance of faujasite‐based catalysts in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 78 publications
(164 reference statements)
2
32
0
Order By: Relevance
“…The computational analysis of the DACD conversion of substituted furans by alkali‐Y zeolites revealed only a minor role of the Lewis acidity of the reactive sites on the catalytic activity, which is to a large extend determined by the geometrical constraints imposed by the size of the cations and the reactants . It was demonstrated that the presence of electron‐donor or acceptor substituents on the furan ring does not have a direct effect on the DACD reactivity.…”
Section: Confinement‐induced Reactivity and Molecular Recognition Phementioning
confidence: 99%
“…The computational analysis of the DACD conversion of substituted furans by alkali‐Y zeolites revealed only a minor role of the Lewis acidity of the reactive sites on the catalytic activity, which is to a large extend determined by the geometrical constraints imposed by the size of the cations and the reactants . It was demonstrated that the presence of electron‐donor or acceptor substituents on the furan ring does not have a direct effect on the DACD reactivity.…”
Section: Confinement‐induced Reactivity and Molecular Recognition Phementioning
confidence: 99%
“…A considerable portion of this biomass is represented by cellulose. This polymer can be hydrolyzed into soluble sugars, and the latter can be used as a feedstock for producing a multitude of chemicals: fuels like bioethanol or biobutanol, biodegradable polymer precursors like levulinic acid, platform chemicals (5‐hydroxymethyl furfural), etc . Catalysis of cellulose hydrolysis by strong mineral acids is well known and efficient, but isolation of the catalyst from the reaction products is complicated .…”
Section: Introductionmentioning
confidence: 99%
“…This polymer can be hydrolyzed into soluble sugars, and the latter can be used as a feedstock for producing a multitude of chemicals: fuels like bioethanol or biobutanol, biodegradable polymer precursors like levulinic acid, platform chemicals (5-hydroxymethyl furfural), etc. [3][4][5][6] Catalysis of cellulose hydrolysis by strong mineral acids is well known and efficient, but isolation of the catalyst from the reaction products is complicated. [7] Enzyme-catalyzed hydrolysis is slow, but the products are suitable for bioprocessing since they are free of acids or byproducts from acidinduced sugar conversion, which are harmful to microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations